1984
DOI: 10.1007/bf00436199
|View full text |Cite
|
Sign up to set email alerts
|

Genetic mapping, cloning and physiological aspects of the glucose kinase gene of Streptomyces coelicolor

Abstract: Glucose kinase in Streptomyces coelicolor has a molecular weight of about 110,000. In crude extracts, the enzyme exhibited apparent Km values of 0.20 mM for ATP, 0.27 mM for glucose, and 2.2 mM for the glucose analogue 2-deoxyglucose. Mutations (glk) to 2-deoxyglucose-resistance, which greatly reduce glucose kinase activity and result in relief of glucose repression of utilisation of various carbon sources, were mapped between proA and hisA in the S. coelicolor linkage map. Glucose kinase activity, 2-deoxygluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0

Year Published

1990
1990
2010
2010

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(48 citation statements)
references
References 28 publications
3
45
0
Order By: Relevance
“…S. coelicolor strain J1508 (hisA1 uraA1 strA1 pglNF, SCP2 negative [21]) was used in all FISH experiments because of the low level of fluorescence emitted by this strain (31). Liquid yeast extract-malt extract (YEME) medium (25 ml) supplemented with 50 g of histidine per ml and 7.5 g of uracil per ml (19) was inoculated with 50 l of an S. coelicolor J1508 spore suspension and incubated at 30°C with vigorous shaking for 40 to 45 h (optical density at 600 nm, ϳ0.7).…”
Section: Methodsmentioning
confidence: 99%
“…S. coelicolor strain J1508 (hisA1 uraA1 strA1 pglNF, SCP2 negative [21]) was used in all FISH experiments because of the low level of fluorescence emitted by this strain (31). Liquid yeast extract-malt extract (YEME) medium (25 ml) supplemented with 50 g of histidine per ml and 7.5 g of uracil per ml (19) was inoculated with 50 l of an S. coelicolor J1508 spore suspension and incubated at 30°C with vigorous shaking for 40 to 45 h (optical density at 600 nm, ϳ0.7).…”
Section: Methodsmentioning
confidence: 99%
“…Glucose repression in S. coelicolor operates at the transcriptional level to repress enzymes involved in the use of glycerol, arabinose, fructose and galactose 122 and this effect seems to be due to either intermediates of carbohydrate catabolism, for example, fructose 1,6-diphosphate and glucose 6-phosphate 123,124 or enzymes of the glucose catabolic pathway, such as glucose kinase. [125][126][127][128] In this regard, it has been reported that mutants of S. coelicolor resistant to the nonutilizable glucose analog, 2-deoxyglucose (DOG), appear to be generally deficient in glucose repression. 122 These mutants (Dog R ) can utilize glycerol, arabinose, fructose and galactose in the presence of glucose.…”
Section: Streptomycesmentioning
confidence: 99%
“…129 Complementation of these mutants with the Glk gene (glkA) restores not only GlkA activity but also DOG sensitivity and partially restores glucose repression. 125,126 Similarly, when the S. coelicolor glkA gene, is introduced into a S. lividans Dog R mutant (unable to utilize glucose and the chitinase production of which is resistant to glucose repression), sensitivity to DOG and the ability to utilize glucose are restored, but glucose repression of chitinase production is only partially recovered. 128 Interestingly, when S. coelicolor Dog R mutants were complemented with the glk gene of the Gram-negative Zymomonas mobilis, Glk activity and glucose utilization are restored, but not glucose repression.…”
Section: Streptomycesmentioning
confidence: 99%
“…Inducible o r constitutive uptake has been reported for several sugars (Sabater et al, 1972;Sabater & Asensio, 1973 ;Hodgson, 1982). Bacteria utilizing glucose, mannose and fructose exhibit activities for ATP-dependent glucokinase, fructokinase and mannokinase (Sabater e t al., 1972;Ikeda e t al., 1984;Angell e t al., 1992) suggesting that transport systems for these sugars are not of the PTS type. At least five different groups have reported evidence leading to the conclusion that the PTS is lacking from the genus Streptomyces (Sabater e t al., 1972;Romano & Margiotta, 1980 ;Novotna & Hostilkk, 1985 ;GarciaDominguez et a/., 1989;L.…”
Section: Introductionmentioning
confidence: 99%